2015
DOI: 10.3109/19396368.2015.1033779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high progesterone on outcomes ofin vitrofertilization-embryo transfer in patients with different ovarian responses

Abstract: The data of 3,841 cycles undergoing in vitro fertilization-embryo transfer (IVF-ET) in our reproductive Center between January 2003 and December 2013 were retrospectively analyzed. According to the number of oocytes retrieved, this study was divided into the high ovarian response group (oocyte retrieval≥20, 842 cycles), the moderate ovarian response group (5 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For those patients, researchers have suggested frozen-thawed embryo transfer or blastocyst transfer. Li et al have demonstrated the effect of high progesterone levels on outcomes of in vitro fertilization-embryo transfer in patients with different ovarian responses (26). They defined a P cut-off value of 2.5 ng/ml in the high ovarian response group, 2.25 ng/ml in the moderate ovarian response group and 1.5 ng/ml in the low ovarian response group.…”
Section: Discussionmentioning
confidence: 99%
“…For those patients, researchers have suggested frozen-thawed embryo transfer or blastocyst transfer. Li et al have demonstrated the effect of high progesterone levels on outcomes of in vitro fertilization-embryo transfer in patients with different ovarian responses (26). They defined a P cut-off value of 2.5 ng/ml in the high ovarian response group, 2.25 ng/ml in the moderate ovarian response group and 1.5 ng/ml in the low ovarian response group.…”
Section: Discussionmentioning
confidence: 99%
“…Although GnRH analogues are frequently used in COS for IVF/ICSI cycles, an elevation in blood P4 levels is frequently noticed near the follicular phase's end. For a number of years, the clinical effect of premature progestrone rise has been extremely contentious, a study's showing that there is no connection between P4 levels and rates of conception (9) , whereas some have noticed a negative impact on cycle results (10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only patients showing a normal ovarian response were included; a poor or high ovarian response may affect the E2 levels, P levels, laboratory outcomes, and clinical outcomes [ 33 37 ]. Moreover, the stimulation protocols and dose of treatment may vary greatly between patients with poor or high ovarian response.…”
Section: Discussionmentioning
confidence: 99%